RESEÑA de : Morales, A.; Fusi, J. P.; de Blas, A. (dirs.). Historia de la nación y del nacionalismo español. Barcelona: Fundación Ortega-Marañón y Galaxia Gutenberg, 2013. - Abad Nebot, Francisco (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2014)
-